The Implementation of Multimodaly to Teach English in RA Nurul Falah - Hidayah, Rohmatul; Aminuddin, Muhammad; Ekawati, Dian; Sajidin, Sajidin (Journal of English Education and Teacher Trainer, 2025)
This study aimed to investigate the implementation of multimodal tools to teach English in kindergarten. The recent study found that it was challenging to teach English as a foreign language for young learners; so that, teachers should provide various activities and improve creativity in teaching. In contrast, from my general observations, drilling was the only method practiced by the teachers to teach English. Nevertheless, this method was not quite fun and engaging for a long term. As the alternative, to overcome the problem, teacher was able to use multimodality to conduct English lesson especially in kindergarten. This research used qualitative descriptive design. The data were collected by interview with verbatim data technique and observation. The investigation showed that English teacher at RA Nurul Falah used several media and activities. These were audio-visual media; which were laptop, flashcard, speaker active and audio media; which was handphone. Besides that, teacher used some techniques. These were learning while playing; learning through running and other movement; learning with watching videos; learning by using with flash cards and learning ask and answer questions to improve their critical thinking. The study showed that the implementation of multimodality could attract and enhanced students’ engagement in the class. Students seemed more fun with many tools usage rather than only implementing drilling method in the class. Moreover, the research also revealed that multimodal usage was better than drilling. It also concluded that the multimodality use in teaching English lessons was useful and beneficial.